Konsep Pendidikan Religio-Humanis Perspektif Soedjatmoko - Al Anhar (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2020)
Soedjatmoko's religious-humanist education concept becomes an educational concept that practically requires a teacher to be sensitive and care about the development and willingness of students. Researchers call it humanist-transcendental education, which is an educational model that gives students freedom of thought based on religious spiritual values. Thus, students should be able to think critically, creatively, innovatively, cooperatively and transcendental, so that their actions always reflect God's goodness. This will also have an impact on a teacher / educator to be more professional, humanist and religious in spirit so that they can become good role models (uswatun hasanah), can be